The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/nau.23525
|View full text |Cite
|
Sign up to set email alerts
|

Sexual function and qualify of life in women with spina bifida: Are the women with spina bifida satisfied with their sexual activity?

Abstract: More than half of sexually active women with spina bifida experience sexual dysfunction. Therefore, health-care providers should pay attention to the symptoms and their management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…A sexual activity rate of 50% among the SB patients in the present study is concordant with previous research [6][7][8]14 that reported rates of sexual activity among women with the same condition ranging from 32% to 68%. This demonstrates important differences compared with the general female population from the countries involved in the study -Brazil and Spain -,which presented sexual intercourse rates ranging from 83.6% to 85.3%.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A sexual activity rate of 50% among the SB patients in the present study is concordant with previous research [6][7][8]14 that reported rates of sexual activity among women with the same condition ranging from 32% to 68%. This demonstrates important differences compared with the general female population from the countries involved in the study -Brazil and Spain -,which presented sexual intercourse rates ranging from 83.6% to 85.3%.…”
Section: Discussionsupporting
confidence: 92%
“…17 The weak median scores found in the overall and specific-domains of the FSFI-6 among our patients are similar to the scores found in previous studies that quantitatively assessed sexuality in a quantitative matter. 8,18 Lee et al 18 found lower overall and specific-domain scores in the FSFI of SB patients when compared with non-SB women who also suffered from sexual dysfunction, showing that these neurologic patients demand more attention to their sexual life than regular patients. 18 To comprehend the sexuality of female patients, it is important to assess their GO aspects.…”
Section: Discussionmentioning
confidence: 99%
“…However, also from the experts’ point of view most of the evidence is anecdotal. In the study performed by Choi et al women who did not suffer urinary incontinence had a better sexual function [ 26 ] regarding pain and lubrication.…”
Section: Diversion Urinary Incontinence and Sexual Lifementioning
confidence: 99%
“…67 Sexual dysfunction is reported in both males and females in approximately 60-80% of cases. 68,69 The incidence of dysfunction does not seem to differ by lesion level for females, but appears to be increased in males with a lower level lesion. 70 Infant Development will be seen in 67% of cases, and significant deficits (<50) in 12%.…”
Section: Ambulation Motor and Sensory Functionmentioning
confidence: 95%
“…Often however, with a dietary and medical bowel regimen along with training, individuals can achieve social continence 67 . Sexual dysfunction is reported in both males and females in approximately 60‐80% of cases 68,69 . The incidence of dysfunction does not seem to differ by lesion level for females, but appears to be increased in males with a lower level lesion 70 .…”
Section: Natural History Of Fetal Spina Bifidamentioning
confidence: 99%